Technical - economic analysis in an individual farm in Olt County - Petruta Turek Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In Romania, the small subsistence farms proved to be very durable. Structural changes led to the multifunctional development of this household, to vegetable marketing, input supply, investments and agricultural works, storage of products. Gradually, the number of subsistence farms will decrease in favour of forming a viable commercial sector and economic diversification in Romanian rural area.
Keywords: 330; average production; commodity production; revenues; expenses; economic size